The impact of digital education on the educational process - Mohamed, Shafizan; Abu Halaqa, Mohamad (2021)
Digital technology affects all facets of human life, including education, Its effect on education and training is unavoidable. A digitally literate citizen will be able to learn and take responsibility for their learning, resulting in a greater demand for education and a greater awareness of the need for more equipment and tools. Integrating technology to help education became a popular topic in the 1990s as the use of the World Wide Web, internet, and intranet expanded. As a result, students can now obtain knowledge no matter where they are in the world. Students may use digital technology to make decisions about their studies, including the time, place, and resources. Students may express their ideas and experiences in a digital world while receiving assistance from other students and teachers. All aspects of electronically assisted learning and teaching are included in the digital classroom. Both networked or not, information and communication systems function as basic media for implementing the learning process. It is essentially the transfer of skills and knowledge through computer and network. Web-based learning, computer-based learning, virtual classroom opportunities, and interactive collaboration are all examples of digital classroom applications that are changing the educational processes. Therefore, students and teachers must be educated and equipped to carry out their responsibilities; schools and organizations must be developed and ready for the new environment.